Möglichkeiten der Strukturierung von Hedgefondsportfolios - Thomas Heidorn; Christian Hoppe; Dieter G. Kaiser (HfB - Business School of Finance & Management, 2005)
The year 2000 started the evolution of the German market for Structured Products with incorporated Hedge Fund exposures. This paper provides an extensive commentary on this fast growing segment. Our analysis suggests that the market for existing products is affected by significant heterogeneity. This heterogeneity relates to amongst others the underlying product and cost structure, the performance and the investment style. The diversity and flexibility that enables the investor to acquire a tailor-made and portfolio-optimized asset allocation, has proven to remain attractive, despite the events of recent years. A new investment act ('Investmentmodernisierungsgesetz') was implemented in Germany in 2004. This means that direct investments in (Fund of) Hedge Funds now compete against Structured Products. However our analysis concludes that these product groups coexist. One reason is the innovation power of financial engineers who continuously create new structured products with specific features.
urn:nbn:de:101:1-2008082706
Keywords: G11; G15; G24; K34; 330; Hedgefonds; Structured Products; Index Certificates; Constant Proportion Portfolio Insurance; Indizes